Large-scale restoration increases carbon stability under projected climate and wildfire regimes - Liang, Shuang; Hurteau, Matthew D; Westerling, Anthony L (Frontiers in ecology and the environment, 2018)
Changing climate and increasing area burned pose a challenge to forest carbon (C) storage, which is compounded by an elevated risk of high-severity wildfire due to long-term fire suppression in the western US. Restoration treatments that reduce tree density and reintroduce surface fire are effective at moderating fire effects and may help build adaptive capacity to changing environmental conditions. However, treatment implementation has been slow and spatially limited relative to the extent of the area affected by fire suppression. Using model simulations, we quantified how large-scale restoration treatments in frequent-fire forest types would influence C outcomes in the Sierra Nevada mountain range under projected climate-wildfire interactions. Our results indicate that large-scale restoration treatments are an effective means of reducing fire hazard and increasing C storage and stability under future climate and wildfire conditions. The effects of implementation timing suggest that accelerated implementation of large-scale restoration treatments may confer greater C-storage benefits, supporting California's efforts to combat climate change.